Mentoring Nurse Scientists to Meet Nursing Faculty Workforce Needs - Mary A. Nies; Meredith Troutman-Jordan (The Scientific World Journal)
Research indicates that mentoring has been highly effective in promoting faculty success. Strong mentors in the area of scholarship are extremely valuable for junior faculty, not only because of their research and academic expertise but also for their role modeling behaviors. This paper highlights key components of research mentoring used by a senior nursing faculty member. The senior faculty mentor and junior faculty mentee developed a common vision, relating to research interests in health promotion for vulnerable populations. Impact at the individual, school, university, and society level is discussed, and benefits of mentoring to meet nursing faculty workforce needs are emphasized.